Rare case of occupational pulmonary hemorrhage in a firefighter. (2022) - Gandhi, Sheiphali A.; Welch, T.J.; Jones, Kirk D.; Cummings, Kristin J.; Styles, Laura; Blanc, Paul D.; Harrison, Robert J.
Abstract: Alveolar hemorrhage associated with physical exertion, known as exercise-induced pulmonary hemorrhage (EIPH), is a rare condition linked to strenuous exertion. This can be an unusual form of respiratory and occupational illness. We present the case of a healthy firefighter who developed fatal pulmonary hemorrhage after participating in a strenuous physical training exercise regimen. This case represents a severe presentation of EIPH, which results from the disruption of the pulmonary blood-gas barrier as a result of strenuous exertion. Clinicians caring for those in vocations and recreation involving extremely vigorous exercise should be aware that such activities can cause EIPH.